Jiangu Granules Regulates Endoplasmic Reticulum Stress-Induced Apoptosis in UMR-106 Cells by Modulating the PERK/eIF2α/ATF4/CHOP Pathway - CHEN Sainan; ZHOU Fen; HUANG Yunmei; LIN Yanping (康复学报)
ObjectiveTo observe and analyze the mechanism by which Jiangu Granules containing serum alleviate endoplasmic reticulum stress (ERS)-induced apoptosis in UMR-106 osteoblast-like cells.MethodsUMR-106 osteoblast-like cells were selected for the study, and various concentrations (0, 0.01, 0.02, 0.03, 0.04, 0.05 μmol/L) of GSK2606414 (PERK inhibitor) were employed to intervene in the cells. The optimal intervention concentration of GSK2606414 was determined using the CCK8 method. UMR-106 cells exhibiting favorable growth status were randomly allocated into four groups: negative control group (NC group), model group (H2O2 group), Jiangu Granules group (H2O2+JG group), and positive control group (H2O2+GSK2606414 group). The NC and H2O2 groups were intervened with 10% saline serum for a duration of 12 hours. The H2O2+JG group was intervened with 10% Jiangu Granules containing serum for 12 hours, while the H2O2+GSK2606414 group underwent intervention with 0.03 μmol/L GSK2606414 and 10% normal saline serum, for 12 hours. The last three groups were supplemented with 10 μmol/L H2O2 solution without altering the new culture medium for 12 hours. The fluorescence expression of GRP78 and Caspase-12 in cells of the NC and H2O2 groups was observed using laser confocal microscopy. Intracellular ROS content was detected using DCFH-DA. The real-time dynamic changes of intracellular calcium ions were observed using laser confocal microscopy to determine whether the ROS/ERS model was constructed. Late apoptosis rate was determined using Annexin V-FITC/PI in the four groups. Additionally, mRNA transcription level and protein expression of ERS related markers GRP78, PERK, eIf2α, ATF4, and CHOP were detected using qPCR and Western blot methods.ResultsIn comparison to the 0 μmol/L group, it was found that 0.03 μmol/L of GSK2606414 had no impact on cell viability after 12 hours of intervention in UMR-106 cells, and this concentration was chosen for subsequent experiments. Compared with the NC group, the H2O2 group showed a significant increase in ROS content (P<0.01). The protein fluorescence expression level of GRP78 and Caspase-12 exhibited a significant increase. Additionally, the intracellular calciumion flow rate demonstrated an accelerated and continuous increase, indicating the successful establishment of the H2O2 induced ROS/ERS model in UMR-106 cells. In comparison to the NC group, the apoptosis rate in the H2O2 group displayed a significant increase (P<0.05). Furthermore, the mRNA transcription level and protein expression level of ATF4 and CHOP, as well as GRP78, PERK, and eIf2α, exhibited a significant increase (P<0.01). Compared with the H2O2 group, the H2O2+JG group and the H2O2+GSK2606414 group showed a significant decrease in the ROS content (P<0.01) and apoptosis rate (P<0.05). The mRNA transcription level (P<0.05) and protein expression (P<0.01) of GRP78, PERK, eIf2α, ATF4, CHOP were significantly down-regulated.ConclusionThese findings suggest that Jiangu Granules can alleviate endoplasmic reticulum stress and reduce apoptosis in osteoblast-like cells through the PERK/eIF2α/ATF4/CHOP signaling pathway, thereby potentially playing a role in the prevention and treatment of postmenopausal osteoporosis.